Aneurysmal benign fibrous histiocytoma of the skin - Bal Amanjit; Punia RPS; Mohan Harsh (Wolters Kluwer Medknow Publications, 2006)
Aneurysmal benign fibrous histiocytoma is a rare variant of benign fibrous histiocytoma. Clinically it has varied appearances and mimic benign and malignant vascular tumors and malignant melanoma resulting in diagnostic difficulties. Histopathological examination is mandatory for diagnosis.